A dimensão retórica e a dimensão discursiva no design gráfico | The rhetorical dimension and the discursive dimension in graphic design - Rati, Bianca Mendes; Beccari, Marcos Namba (InfoDesign, 2020)
O objetivo deste artigo é explorar diferenças e construir pontes entre a dimensão retórica e a dimensão discursiva (na perspectiva foucaultiana) no design gráfico. A ideia é justapor uma abordagem já comum e outra pouco utilizada na área, e assim buscar entender suas finalidades. Para isso, fez-se uma breve introdução aos conceitos principais de ambas dimensões e suas aplicações. Após isso, realizou-se uma análise de três artefatos (peça publicitária, pictogramas e infográfico) considerando as perspectivas apresentadas e seus critérios. Conclui-se que a abordagem discursiva difere da retórica pois não se concentra apenas nos aspectos semânticos das linguagens e sim, propõe que o discurso, para Foucault, regula as conotações e denotações consideradas possíveis. ***** The purpose of this article is to explore differences and build bridges between the rhetorical dimension and the discursive dimension (in a Foucaultian perspective) in graphic design. The idea is to juxtapose an already common approach to another little used in the area, and thus seek to understand its purposes. For this, a brief introduction to the main concepts of both dimensions and their applications was made. After that, an analysis of three artifacts (advertising piece, pictograms and infographic) was performed considering the presented perspectives and their criteria. We conclude that the discursive approach differs from rhetoric because it focuses not only on the semantic aspects of languages but rather proposes that, under the Foucault’s bias, discourse regulates the connotations and denotations considered possible.